2022
DOI: 10.1039/d1fo03320d
|View full text |Cite
|
Sign up to set email alerts
|

The anti-fatigue effect of the Auxis thazard oligopeptide via modulation of the AMPK/PGC-1α pathway in mice

Abstract: In this study, the anti-fatigue effect and mechanism of Auxis thazard oligopeptide (ATO) were studied by exhaustive swimming in mice. The results showed that ATO could significantly prolong the exhaustive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…However, low-dose YPLP had no significant effect on the exercise tolerance. Qu et al found that the exercise time to exhaustion of medium-dose ( Auxis thazard ) oligopeptide group was longer than low- and high-dose groups in exercise mice. Therefore, the exercise tolerance of mice is related to the gavage dose of the bioactive peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, low-dose YPLP had no significant effect on the exercise tolerance. Qu et al found that the exercise time to exhaustion of medium-dose ( Auxis thazard ) oligopeptide group was longer than low- and high-dose groups in exercise mice. Therefore, the exercise tolerance of mice is related to the gavage dose of the bioactive peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have revealed that many bioactive peptides, such as seahorse-derived peptides and tuna-derived peptides, participated in the AMPK signaling pathway to alleviate fatigue. 5,6 In our previous research, YPLP has been shown to participate in the AMPK/PGC-1α pathway to enhance the ATP level and mitochondrial function in C2C12 myotube cells. 10 The current study reveals that YPLP improved energy metabolism via involvement in the AMPK/ PGC-1α pathway in exercise mice.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…In addition, AMPK/PGC-1α are the curial regulatory factors in mitochondrial metabolism, which is highly related to exercise tolerance. 27 AMPK is activated to promote energy metabolism including glycogen absorption and fatty acid oxidation during exercise. 27 One of the key downstream targets, coactivator PGC-1α regulates the bioenergetic efficiency of glucose oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…27 AMPK is activated to promote energy metabolism including glycogen absorption and fatty acid oxidation during exercise. 27 One of the key downstream targets, coactivator PGC-1α regulates the bioenergetic efficiency of glucose oxidation. 28 Based on functional enrichment and pathway analysis of BE, the Nrf2/HO-1 and AMPK/PGC-1α signaling pathways were focused on as the mechanisms by which BE achieves anti-fatigue effects.…”
Section: Resultsmentioning
confidence: 99%